Penerapan Socio Scientific Issues (SSI) untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Kelas VII di Era Revolusi Industri 4.0 - Zahroh, Mu'nisatuz; Hidayati, Siti Nurul; Aulia, Ernita Vika (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to describe the increase in students' problem-solving abilities after implementing learning using the Socio Scientific Issues approach.Method – The research was conducted using a pre-experimental design with a one group pretest and posttest design. This research adopted the 2012 OECD problem-solving ability indicators with the research subjects consisting of 33 grade 7 students at MTsN Gresik. The data collection method used was the test method and analyzed using quantitative descriptive. Research shows an increase in problem solving abilities analyzed using the N-Gain test.Findings – The research results show that the N-Gain value for the Exploring and Understanding indicator is 0.89, which is included in the high category. The Representing and Formulating indicator has an N-Gain value of 0.54, which is included in the medium category. The Planning and Executing indicator show an N-Gain value of 0.64, also included in the medium category. Meanwhile, the Monitoring and Reflecting indicator has an N-Gain value of 0.53, included in the medium category. Research Implications – The use of problem orientation and this learning model can be applied to science material from other chapters which also presents controversial social issues and requires the involvement of students' analytical and critical thinking skills.